Force sensors to reduce lower limb asymmetry in rowers - Kulkarni, N.; Kaur, S.; Wadzinski, E.; Topercer, B.; Ryan, O.; Bhatia, S. (University of Wisconsin-Madison: Department of Biomedical Engineering, 2023)
Problem Statement Rowing athletes, particularly women, are susceptible to lower back or hip injuries • Asymmetric weight distributions on each leg while rowing